Los procesos matrimoniales en los tribunales eclesiásticos españoles. Reflexión sobre las estadísticas de la Iglesia en España - Guzmán Pérez, Cristina (Estudios eclesiásticos, 2009)
The present work, to better understand the functioning of the ecclesiastical courts, encloses some reflections on the latest statistical data provided by the Spanish Episcopal Conference. For that purpose, the most significant data has been selected, including the whole number of procedures submitted, the court decisions accepting the nullity of marriage and their causes, as well as their economic costs and their duration.